Changing our Diagnostic Paradigm Part II: Movement System Diagnostic Classification - Paula M Ludewig; Gaura Saini; Aaron Hellem; Emily K Kahnert; S Cyrus Rezvanifar; Jonathan P Braman; Justin L Staker (International Journal of Sports Physical Therapy)
Diagnostic classification is a foundational underpinning of providing care of the highest quality and value. Diagnosis is pattern recognition that can result in categories of conditions that ideally direct treatment. While pathoanatomic diagnoses are common and traditional in orthopaedic practice, they often are limited with regard to directing best practice physical therapy intervention. Replacement of pathoanatomic labels with non-specific regional pain labels has been proposed, and occurs frequently in clinical practice. For example non-specific low back pain or shoulder pain of unknown origin. These labels avoid some disadvantages of tissue specific pathoanatomic labels, but are not specific enough to direct treatment. A previously introduced movement system diagnostic framework is proposed and updated with application to shoulder conditions. This framework has potential for broad development and application across musculoskeletal physical therapist practice. Movement system diagnostic classification can advance and streamline practice if considered while recognizing the inherent movement variability across individuals.